Case report: two cases of spontaneous intramural duodenal hematoma associated with pancreatitis - Ljubicic, Lidija; Romic, Ivan; Petrovic, Igor; Marusic, Zlatko; Silovski, Hrvoje (Acta Biomedica Atenei Parmensis, 2022)
Intramural duodenal hematoma (IDH) is a rare entity and is generally associated with trauma. Spontaneous (nontraumatic) intramural duodenal hematoma is associated with bleeding disorders, anticoagulation therapy, alcoholism, pancreatitis, tumours  and duodenal ulcers. We report two cases of spontaneous intramural duodenal hematoma in middle-aged men who subsequently developed pancreatitis. The underlying pathophysiology is still unclear. In the cases described, it is not clear whether the intramural duodenal hematoma contributed to the development of pancreatitis or pancreatitis has contributed to the development of IDH.